The clinical significance of echo-attenuated plaque in stable angina pectoris compared with acute coronary syndromes: A combined intravascular ultrasound and optical coherence tomography study. (1st November 2018) - Kimura, Shigeki; Sugiyama, Tomoyo; Hishikari, Keiichi; Nakagama, Shun; Nakamura, Shun; Misawa, Toru; Mizusawa, Masafumi; Hayasaka, Kazuto; Yamakami, Yosuke; Sagawa, Yuichiro; Kojima, Keisuke; Ohtani, Hirofumi; et al.
Abstract: Background: Echo-attenuated plaque (EA) on intravascular ultrasound (IVUS) is related to poor outcomes after percutaneous coronary intervention (PCI) in acute coronary syndrome (ACS) patients. However, the clinical significance of EA in stable angina pectoris (SAP) patients compared with that in ACS patients remains unclear. We assessed the relationships between EA and unstable plaque characteristics in patients with ACS and SAP. Methods: We investigated 609 coronary lesions in 609 patients (234 with ACS; 375 with SAP) undergoing pre-intervention IVUS and optical coherence tomography (OCT). The differences in plaque morphology and post-PCI outcomes were assessed according to the clinical status of ACS or SAP and the presence or absence of EA. Results: EA was more frequent in patients with ACS than in those with SAP (44.0% vs. 25.1%, p < 0.001). SAP-EA lesions showed thicker fibrous cap (157 ± 97 μm vs. 100 ± 58 μm, p < 0.001), smaller lipid arc (208 ± 76° vs. 266 ± 99°, p < 0.001), smaller plaque burden (83.0 ± 6.1% vs. 86.5 ± 4.1%, p < 0.001), and lower frequency of transient slow-reflow phenomenon during PCI (21.3% vs. 51.5%, p < 0.001) than ACS-EA lesions, but similar plaque vulnerability compared with ACS-non-EA lesions. SAP-EA lesions had less frequent OCT-thrombus than ACS-non-EA lesions (20.2% vs. 71.2%, p < 0.001). Conclusions: SAP-EA lesions had less plaque vulnerability than ACS-EA lesions, but were comparable to ACS-non-EA lesions. Less frequent thrombus formation might differentiate SAP-EA lesions from ACS-non-EA lesions. A combined IVUS and OCT approach might be useful to assess plaque vulnerability in SAP-EA lesions compared with ACS lesions. Highlights: We assessed the relationships between EA in SAP lesions and ACS plaques. SAP-EA lesions had less plaque vulnerability than ACS-EA lesions. SAP-EA lesions had a similar plaque vulnerability to ACS-non-EA lesions. Fewer thrombi might prevent SAP-EA lesions from causing ACS events. A combined IVUS and OCT approach might be useful to clarify plaque vulnerabilities.